Civil engineering education and training 1976 proceedings of a conference organized by the Institution of Civil Engineers and held in Swansea on 23 and 24 September, 1976 - Darwent, Thelma J. (Telford for the Institution, 1977)
The author of this paper highlights the value of education of professional engineers in Britain and on the continent. He discusses the aim of the paper, preparation at school and for professional practice, looks at engineering curricula in Europe and Russia, focuses on the breadth and depth of studies, and concludes with a comment about France and the future.